New cirripedes (Crustacea, Thoracica) from the Campanian (Upper Cretaceous) of the Hannover area, Germany - Gale, Andy S.; Jagt, John W.m. (Zootaxa, 2026)
Two new species of pedunculate cirripede are described from lower Campanian basinal limestones of Höver and Misburg (Hannover area), northern Germany. These are the myolepadid Bosquetlepas schneideri sp. nov. and the large cretiscalpellid Jagtscalpellum kaeckei sp. nov. The occurrence of Bosquetlepas in basinal limestones is remarkable, as the genus was largely confined to shallow-marine and coastal habitats.